2022
DOI: 10.1002/sim.9511
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of stepped wedge cluster randomized trials in the presence of a time‐varying treatment effect

Abstract: Stepped wedge cluster randomized controlled trials are typically analyzed using models that assume the full effect of the treatment is achieved instantaneously. We provide an analytical framework for scenarios in which the treatment effect varies as a function of exposure time (time since the start of treatment) and define the “effect curve” as the magnitude of the treatment effect on the linear predictor scale as a function of exposure time. The “time‐averaged treatment effect” (TATE) and “long‐term treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 39 publications
1
24
0
Order By: Relevance
“…This supports the general recommendation of including time × group random effects in the analysis of multiple period GRT data as there is little indication of any penalty of having it and the potential for a substantial problem if left out. This is consistent with other findings in the literature suggesting that the drawbacks of overfitting tend to be less severe than those associated with under-fitting [35][36][37].…”
Section: Discussionsupporting
confidence: 92%
“…This supports the general recommendation of including time × group random effects in the analysis of multiple period GRT data as there is little indication of any penalty of having it and the potential for a substantial problem if left out. This is consistent with other findings in the literature suggesting that the drawbacks of overfitting tend to be less severe than those associated with under-fitting [35][36][37].…”
Section: Discussionsupporting
confidence: 92%
“…For example, in a stepped-wedge CRT assessing the effect of exercise on clinical depression, the full effect may take weeks or months to reach. As another example, Kenny et al (2022) conducted a secondary analysis of data from the Washington State Community-Level Expedited Partner Treatment (EPT) Randomized Trial, which sought to test the effect of EPT, an intervention in which the sex partners of individuals with sexually transmitted diseases are treated without evaluation, on rates of chlamydia and gonorrhea (Golden et al, 2015). When the instantaneous and sustained treatment effect was assumed, the parameter estimates indicated a small beneficial treatment effect.…”
Section: Introductionmentioning
confidence: 99%
“…If the form of exposure-time treatment effect heterogeneity is known a priori, one can proceed by modeling the treatment effect as an explicit, parametric function of exposure time. For example, Hughes et al (2015) proposed fixed-effects parameterizations which include delayed, linear-time, and exponential-time treatment effect functions, and Kenny et al (2022) further developed overall summary measures based on such time-specific treatment effects. The knowledge of the true functional form for exposure-time treatment heterogeneity, however, may not be available in practice.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is of interest to further explore design and analysis strategies for SW‐CRTs with multivariate outcomes when the intervention effects are unknown functions of the exposure time. Under the SW‐CRT design with a single primary endpoint, Kenny et al 31 found that assuming an immediate treatment effect when the true treatment effect is a function of exposure time can lead to estimation bias and invalid inference. It is likely that the same conclusion would apply to the multivariate linear mixed models with more than one primary endpoint.…”
Section: Discussionmentioning
confidence: 99%